Pengaruh Kepercayaan Diri Terhadap Hasil Belajar Siswa pada Mata Pelajaran Matematika Kelas V SDN Dukuh - Hasanah, Uswatun; Priyatno, Agus; Firmansyah, Willis (AL - KAFF: JURNAL SOSIAL HUMANIORA, 2022)
This research is motivated by the weak self- confidence of students in the learning process in class. Based on observations on Mathematics subjects the teacher does not use interesting learning media. The purpose of this study was to determine the effect of self-confidence on student learning outcomes in the fifth grade of SDN Hamlet in Mathematics. The method used is functional correlation using regression analysis by collecting data through a questionnaire, data presented in the form of numbers and values. It can be concluded that there is an effect of self-confidence on the mathematics learning outcomes of Dukuh Elementary School students. This can be proven by obtaining the value of count> table (6.156> 1.734), so that H0 is rejected, which means that confidence affects the learning outcomes.